The Seventeenth-Century Terrestrial Globe by Morden, Berry and Lea. Issue Volume 71:Issues 1(2019) (2nd January 2019) - Perkins, Emma
ABSTRACT: Throughout the early modern period, the intellectual and symbolic value of globes ensured these objects enjoyed a broad cultural appeal. Consequently, their design was subject to a wide range of social, commercial and intellectual pressures. The ways in which the intellectual and cultural concerns of seventeenth-century England became manifest in the cartographic design, resulting in a culturally specific product with broad appeal to an English audience, are highlighted in the case of a terrestrial globe constructed by Robert Morden, William Berry and Philip Lea, c .1683−1690, now in the Whipple Museum, Cambridge. Since this particular globe was produced at an early stage in the history of English globe making, light is shed on the emergence of a national globe-making tradition.